Research on prescribing cascades: a scoping review - Chen, Zhe; Liu, Zheng; Zeng, Linan; Huang, Liang; Zhang, Lingli (Frontiers in Pharmacology, 2023)
Background: The concept of prescribing cascades has been proposed for more than 20 years, but the research progress and cognitive level varied in different countries. The aim of this study was to systematically evaluate the current status of relevant original research on prescribing cascades, and to provide references for further research and continuous improvement in clinical practice. Methods: We searched three English databases and four Chinese databases from inception until January 2022. Relevant studies about prescribing cascades meeting the eligibility criteria were extracted independently by two reviewers, and a descriptive analysis was conducted to compare the methods and outcomes of the included studies. Results: A total of 32 studies involving 7,075,200 patients in 11 countries were included, including 13 cross-sectional studies, 11 case reports, 7 cohort studies, and 1 case-control study. The target population was mainly elderly people (24 studies). The purpose of the included studies could be divided into three categories: prevention (4 studies), identification (17 studies), and resolution (11 studies) of prescribing cascades. 49 prescribing cascade routes were identified and mainly attributed to the cardiovascular system, most primary diseases of which were dementia, the initial medications of prescribing cascades were mainly calcium channel blockers, and two to six drugs were involved in the prescribing cascade routes. Conclusion: Prescribing cascades have attracted more attention internationally and current studies have mainly focused on the elderly and their cardiovascular diseases and nervous diseases, but still not yet formed integral research in other special populations of drug use, such as children and pregnant women. It is necessary to further conduct in-depth studies with a broader range, and to establish a series of effective measures to decrease the incidence of prescribing cascades in the high-risk group of drug use.